2019
DOI: 10.1111/aogs.13705
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Doppler ultrasound in predicting perinatal outcome in pregnancies at term: A prospective longitudinal study

Abstract: Introduction: To explore the strength of association and the diagnostic accuracy of umbilical (UA), middle cerebral (MCA), uterine arteries pulsatility index (PI) and the cerebroplacental ratio in predicting an adverse outcome when applied to singleton pregnancies at term. Material and methods: Prospective study carried out in a dedicated research ultrasound clinic. Attended clinicians were blinded to Doppler findings. Inclusion criteria were consecutive singleton pregnancies between 36 +0 and 37 +6 weeks of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Conversely, a decrease in MCA PI has been shown in up to 20% of late FGR with a normal UA PI [1] and has been reported to be associated with poor short- and long-term outcomes, such as stillbirth, CD for fetal distress, and abnormal neurodevelopment at birth and at 2 years [23-26]. In 1987, the ratios between these 2 parameters (CPR and UCR) were described and henceforth have been claimed to be even more accurate in predicting perinatal morbidity and mortality, detecting subtle changes that could remain potentially inappreciable when exploring UA or MCA individually [27, 28]. The CPR has been more often evaluated than the UCR and incorporated in clinical guidelines, given its easier interpretation to clinicians due to its normal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a decrease in MCA PI has been shown in up to 20% of late FGR with a normal UA PI [1] and has been reported to be associated with poor short- and long-term outcomes, such as stillbirth, CD for fetal distress, and abnormal neurodevelopment at birth and at 2 years [23-26]. In 1987, the ratios between these 2 parameters (CPR and UCR) were described and henceforth have been claimed to be even more accurate in predicting perinatal morbidity and mortality, detecting subtle changes that could remain potentially inappreciable when exploring UA or MCA individually [27, 28]. The CPR has been more often evaluated than the UCR and incorporated in clinical guidelines, given its easier interpretation to clinicians due to its normal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, the incidence of adverse perinatal outcome was calculated to be 19.4%, which was a little higher than the 17.9% by Fiolna et al (13), 9.5% by Antonio et al (14), and lower than 28.5% by Asta et al (15). We considered that the different inclusion criteria, cohort characteristics, races, and the de nitions of adverse perinatal outcome were the main explanations for the different results.…”
Section: Discussionmentioning
confidence: 58%
“…We have recently reported that MCA and CPR are not predictive of adverse outcome in an unselected population of singleton pregnancies at term [8].…”
Section: Introductionmentioning
confidence: 89%
“…The study was approved by the local IRB (approval number: rich5j7v9). The present study shares part of its population with that of our recently published study exploring the diagnostic accuracy of fetal Doppler for predicting perinatal outcome once applied to an unselected population of singleton pregnancies close to or at term [8].…”
Section: Methodsmentioning
confidence: 99%